Idiopathic Parkinson Disease and Its Homoeopathic Management (Homoeopathy for All, 2021)
Parkinson’s disease (PD) was first described by Dr. James Parkinson in 1817 as a “shaking palsy.” It is a chronic, progressive neuro-degenera tive disease characterized by both motor and nonmotor features. The term parkinsonism is a symptom complex used to describe the motor features of PD, which include rest ing tremor, bradykinesia, and mus cular rigidity.
Keywords: Aetiology; Pathophysiology